Dominance and growth of Diplodus sargus (Pisces: Sparidae) in small captive groups - Gonçalves, Ana Sofia Ribeiro (2013)
The dominance hierarchies and the growth rate of the commercially important fish Diplodus sargus were assessed in this study. Specifically, we tested the hypothesis that, if stable dominance orders were established, dominant fish would grow faster and show better condition factors than losers at the end of the experiment. Eight groups of six individuals were followed for 6 weeks and, for each group, we measured the linearity of the hierarchies on a weekly basis, and the week to week stability of the hierarchical structures. These dominance structures were linear and stable from week to week. We found no significant correlation between the dominance index with either growth rate or final condition factor. Thus, in short time windows over few weeks, aggressive competition seems not to cause differences in growth, although effects at a longer term like those induced by stress cannot be ruled out.